EFFECT OF FIRST LOW WAGES’ JOB ON THE SELF-ESTEEM OF PAKISTANI MIDDLE-CLASS FRESH GRADUATES - Tariq, Amina; Farooqi, Rabia (PEOPLE: International Journal of Social Sciences, 2018)
In Pakistan, the number of educated people at graduate level is quite high but according to that number employments are limited. This causes job dissatisfaction and also abolishes the relationship with the co-workers (Farooq, Ahmad, & Ali, 2008). This study aimed to explore the effect of first low wages’ job on self-esteem of Pakistani fresh graduates in terms of satisfaction level, hope level, productivity and wellbeing using a constructivist grounded theory approach (Charmaz, 2014). In this study qualitative approach is used. For data collection, purposive sampling technique was used along with the semi structured interviewing from local private schools. Four female teachers with an age range of 20- 25 years were the sample of the study. One-to-one interviews with the participants were conducted after taking their permission to participate voluntarily in the research, and tape recording of their interviews for transcription of data. Grounded theory approach was used to analyze collected data as no work has been done in Pakistan in this context and I want to develop theory which will be helpful in employer’s context and working satisfaction. For reliability check, triangulation method was used. The theory of self-esteem grounded here suggested that first low wages’ job for the Pakistani fresh graduates has negative effect on the level of hope and satisfaction whereas their productivity and wellbeing has positive effect on them.